Pengaruh Kompetensi dan Motivasi Kerja Terhadap Kinerja Pegawai Badan Pusat Statistik Kebupaten Ciamis - Ading Rahman Sukmara; Ade Pudiaman; Irma Bastaman (Journal of Management and Social Sciences, 2024)
The purpose of the study was to determine and describe (1) the competence, motivation, and performance of employees of the Ciamis Regency Statistics Agency, (2) the influence of competence on employee performance at the Ciamis Regency Statistics Agency, (3) the influence of motivation on employee performance at the Ciamis Regency Statistics Agency, and (4) the influence of competence and motivation on employee performance at the Ciamis Regency Statistics Agency. With the formulation of the problem how the research objectives are formulated. The method used in this study is descriptive and verification research. Based on the results of the research and discussion, the following conclusions were obtained. The competence of BPS employees based on respondents is included in the good category, with the highest indicator being the attitude indicator with an average score of 144.33 or 78.01% (in the good category) while the lowest average score occurred in the knowledge indicator of 135 or 72.97% (in the good category). The results of data processing show that the competence of BPS employees has a positive effect on employee performance at the Ciamis Regency Statistics Agency. This means that if there is an increase in competence and motivation, it will be followed by an increase in employee performance. With competence and motivation that continue to increase, employee performance will increase further. The work motivation of BPS employees based on respondents is included in the good category, with the work motivation indicator being the indicator of the need for power with the highest average score of 148 or 80% in the good category while the lowest average score is in the indicator of the need for achievement of 145 or 78.70% in the good category. If presented as a whole, the respondents' responses to work motivation are 77.89% when compared to table 4.28. then it is in the 4th interval which means that the respondents' responses to employee performance are included in the good category. The results of data processing show that employee work motivation has a positive effect on employee performance at the Central Statistics Agency of Ciamis Regency. This means that if there is an increase in competence and motivation, it will be followed by an increase in employee performance. With increasing competence and motivation, employee performance will increase. Competence and motivation have a positive effect on employee performance at the Central Statistics Agency of Ciamis Regency. This means that if there is an increase in competence and motivation, it will be followed by an increase in employee performance. With increasing competence and motivation, employee performance will increase.